Benefits of sea buckthorn juice consumption in women of productive age with hypercholesterolemia - Jana Kopčeková; Jana Mrázová; Katarína Fatrcová-Šramková; Marta Habánová; Martina Gažarová; Petra Lenártová (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. Sea buckthorn contains almost 200 nutrients and bioactive substances, including phenolic compounds such as flavonoids, vitamins, proteins, amino acids, minerals, alkaloids, chlorophyll derivatives, amines, organic acids, fatty acids and phytosterols. Human and animal studies suggest that sea buckthorn may have a variety of beneficial effects: cardioprotective, antiatherogenic, antioxidant, anticancer, immunomodulatory, antibacterial, antiviral and antiinflammatory. Objective. The aim of this study was to evaluate the effect of regular consumption of 100% sea buckthorn juice on the risk factors of cardiovascular diseases in women of productive age with hypercholesterolemia. Material and Methods. A clinical study involved 19 women with a mean age of 54.06 ±2.97 years who consumed 50 mL of sea buckthorn juice daily for 8 weeks. Anthropometric and biochemical parameters in blood serum were monitored before the start of sea buckthorn consumption and after 8 weeks of consumption. Body composition was determined using an multifrequency analyzer InBody720. Routine biochemical analyzes were performed by standard methods in an accredited laboratory of the University Hospital by automatic biochemical analyzer BioMajesty JCA-BM6010/C. Statistical comparison between individual measurements was performed using a paired t-test, using Statistica Cz version 10 (TIBCO Software, Inc., Palo Alto, CA, USA). Results. We observed significant decrease of body weight, body mass index (P<0.05), body fat and visceral fat (P<0.001) after 8 weeks of consumption of 100% sea buckthorn juice. In this intervention study, we observed a significant decrease in low-density cholesterol (P˂0.05) and a significant increase in high-density cholesterol (P˂0.001). The level of triglycerides was similar at the end of the study (P>0.05). After the intervention, we observed decrease of orosomucoid, immunoglobulin A, immunoglobulin G, immunoglobulin M (P<0.001) and C-reactive protein (P<0.01). Conclusions. The obtained results support the hypothesis that the daily consumption of sea buckthorn juice for eight weeks could contribute to the beneficial effects of reducing the risk of cardiovascular diseases, such as the reduction of body and visceral fat, LDL-C, CRP and the increase of HDL-C.